2012
DOI: 10.1074/jbc.m112.352096
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Characterization of NikO, an Enolpyruvyl Transferase Essential in Nikkomycin Biosynthesis

Abstract: Background: Nikkomycins are potent antibiotics. NikO is a key enzyme in their biosynthesis. Results: NikO is structurally closely related to other enolpyruvyl transferases and is inhibited by fosfomycin. Conclusion: Conservation of important active site residues indicates mechanistic similarities to MurA. Significance: The structure of NikO is the first of an enzyme participating in the formation of the aminohexuronic acid moiety in nikkomycin biosynthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 49 publications
(33 reference statements)
1
8
0
Order By: Relevance
“…145,146 The orthologous enzymes encoded by nikO 147,148 and polA 145 have been shown to catalyze the formation of 3′-enoylpyruvoyl-UMP from PEP ( 108 ) and UMP in assays with purified recombinant proteins. Gene knockout experiments demonstrated that nikO 149 and sanX 146 are required for the biosynthesis of nikkomycins and that polA is required for the biosynthesis of polyoxins.…”
Section: Compounds Containing High-carbon Sugarsmentioning
confidence: 99%
“…145,146 The orthologous enzymes encoded by nikO 147,148 and polA 145 have been shown to catalyze the formation of 3′-enoylpyruvoyl-UMP from PEP ( 108 ) and UMP in assays with purified recombinant proteins. Gene knockout experiments demonstrated that nikO 149 and sanX 146 are required for the biosynthesis of nikkomycins and that polA is required for the biosynthesis of polyoxins.…”
Section: Compounds Containing High-carbon Sugarsmentioning
confidence: 99%
“…These values are comparable to those reported for the conversion of UMP to EP-UMP by NikO ( k cat / K m = 0.10 – 0.45 min −1 µM −1 ). 13 The low K m values support high specificity of NikJ and PolH towards EP-UMP. Together with the previously established relevance of octosyl acid to PN biosynthesis, 5 7 these observations suggest that the observed OAP synthase activity is likely the physiologically relevant function of NikJ and PolH.…”
mentioning
confidence: 91%
“…NikO was shown to transfer the enol-pyruvyl moiety from PEP to the 3′-hydroxyl group of UMP and to be inactivated by fosfomycin because of alkylation of Cys130. However, the degree of inactivation is not as pronounced as in the case of common MurA enzymes [23].…”
Section: Enol-pyruvylation In Peptidoglycan Biosynthesismentioning
confidence: 99%